Performance of different seed metering devices to corn crops (Zea mays L.) according to planting speed (Semiárida, 2017)
In order for a crop to show its full yield potential, it needs not only adequate weather and soil conditions but also good implantation quality enhanced through emerged plant density with respect to the amount of seeds sown as well as during these seed uniform distribution along the sowing lines. The set up and adjustment of the seed drills used are involved in this process, being the seed metering devices and work speed basic elements to be taken into account. In this study, the performance of a mechanical dosing machine functioning with horizontal plates and the performance of another pneumatic device functioning by means of suction and with vertical plates were measured, both operating at 5, 7 and 9 km.h-1. Tests were carried out on test benches and field tests applying specific protocols for the precision seed drill trials measuring the emerged plant population and the uniformity in the distribution along the sowing lines. The statistical data analyses showed no significant differences in the number of emerged plants as well as in the spatial arrangement in the sowing lines when the dosing machine and the planting speed were compared separately and during interaction. Nevertheless, a tendency towards improving these figures when operating at intermediate speed with both seed metering devices was noticed. DOI: http://dx.doi.org/10.19137/semiarida.2016(02).27-37
Keywords: Pneumatic seed metering devices; mechanical seed metering devices; spatial arrangement